Persepsi Masyarakat Terhadap Sumbangan Wajib Dana Kecelakaan Lalu Lintas Jalan Dan Kebijakan Perlindungan Kecelakaan Jalan - Sitorus, Budi; S. Sitorus, Antoni; Irpan Harsono , Tulus; Natalia Sitorus, Christina (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2022)
Safety is an important part in using motor vehicles and public transportation, where in 2019 the road transport mode ranks third after the flight mode and cruise mode with a contribution of 24.9%, for that safety can be a safe culture in travel. The purpose of the study was to determine the perception of society related to SWDKLLJ and the level of community satisfaction. The research method is using qualitative descriptive approach with data collection using Gay and Diehl data collection techniques with a sample of 28 respondents, using google form. This data collection was given randomly to respondents and secondary data was obtained from literature and research results to support this study. The results showed that (1) knowledge about iruan SWDKLLJ majority of respondents do not know as much as 51.9%, (2) utilizing the mandatory donation of road traffic accident funds (SWDKLLJ) the majority of respondents are not as much as 88.9%, (3) other insurance funding as a replacement, the majority of respondents answered No 44%, (4) Officer services in making claims using SWDKLLJ, the majority of respondents answered quite satisfied 44%. Further studies are needed to reveal the public satisfaction of swdkllj contribution services and highway safety protection policies.